2006
DOI: 10.1007/s00787-005-0516-1
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and depression. Comparative course in adolescents

Abstract: Depressive states and substance use in adolescents can vary considerably overtime, and are closely but rather synchronically related. Since most of the adolescents do not seek help for substance-related problems, substance use should be systematically assessed in adolescents presenting with a depressive state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
5
18
0
3
Order By: Relevance
“…Brook et al 1998;Chinet et al 2006;Henry et al 1993). This is in line with the results of the current study which found a positive correlation between initial levels of depressive symptoms and substance misuse.…”
Section: Relationship Between Depression and Substance Misusesupporting
confidence: 95%
See 1 more Smart Citation
“…Brook et al 1998;Chinet et al 2006;Henry et al 1993). This is in line with the results of the current study which found a positive correlation between initial levels of depressive symptoms and substance misuse.…”
Section: Relationship Between Depression and Substance Misusesupporting
confidence: 95%
“…Costello et al 1999;Newcomb et al 1986;Henry et al 1993), whereas other studies have indicated that substance use problems in adolescents predict the development of subsequent depressive disorders (Brook et al 1998;Hansell and Raskin White 1991). At the same time, several studies that have found no prospective relationship, in either direction, between depression and substance use problems (Chinet et al 2006;McGee et al 2000). All of these prospective studies have examined predictive relationships between depression and substance use problems over a longer follow-up period (i.e.…”
Section: Relationship Between Depression and Substance Misusementioning
confidence: 95%
“…Previous studies of the association between depression and substance use in adolescents are limited by cross-sectional design or, when longitudinal, by using non-representative samples, short time periods, or not examining both directions or sex differences (Brook, Brook, Zhang, Cohen, & Whiteman, 2002; Chinet et al, 2006). This paper prospectively examines directionality over a longer time period using the population-based Add Health sample and stratifying by sex.…”
Section: Introductionmentioning
confidence: 99%
“…Comorbid major depression has also been found to associate with earlier alcohol relapse among adolescents with alcohol use disorders [31] . Chinet et al [32] recently reported a decrease in depressive symptoms among adolescents who decreased their substance use. Even though the temporality/causality of these disorders has remained unclear, in the light of present research it is fair to conclude that clinicians treating adolescents with either disorder should also focus attention on the possible presence of the other.…”
Section: Discussionmentioning
confidence: 99%